Polos de diferenciales regulares sobre curvas singulares (2011)
bstract: In algebraic Geometry, an algebraic curve is an algebraic variety of dimension one. The Theory of Ã © hese curves was generally well developed in the nineteenth century. The regular differential projective algebraic curve may have poles in their model does not unique. In Ã © ste paper looks at the poles of a regular differential algebraic curve of a complete and irreducible invariant Ringtones © Terms of discrete local rings. Also © n addresses the Cartier operator and zeta function will, which encodes important properties of the curve. This consequence of the Riemann-Roch theorem, local duality and the reciprocity law for singular curves.